Untranslated region-5' and viral protein 1-based genetic stability analysis of bulk polio in Indonesia 2010-2019 - Andi Yasmon; Normasari Normasari; Fithriyah Fithriyah; Fadilah Fadilah (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2021)
Cases of vaccine-associated paralytic poliomyelitis (VAPP) continued increasingly from 2010-2019 in the world. Oral polio vaccine (OPV) is the live attenuated virus-based vaccine that could genetically revert to neurovirulent during the vaccine production process or when the virus replicates in the human body. The poliovirus neurovirulence is determined by the UTR-5' region and VP1 coding region. UTR-5' played a role in protein translation and VP1 was responsible for the immunogenicity of the virus. Some reported mutations in UTR-5' and VP1 could affect the neurovirulence of poliovirus. In this study, we analyzed the genetic stability of the UTR-5' and VP1 in the bulk of OPV types -1 and -3 produced in 2010 - 2019. The results of the analysis of UTR-5' sequences in Sabin strain types-1 and -3 and VP1 sequences on Sabin virus type 1 did not show any mutations. Meanwhile, the VP1 sequences in Sabin strain type 3 showed nucleotide mutation C2493U that caused the substitution amino acid Thr6Ile amino acid in all samples of the type 3 bulk polio test. Based on the results of in silico analysis, this mutation in VP1 did not contribute significantly to the neurovirulence of the virus.